(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The critical analysis hypothesis on Rimini Protokoll’s Remote Buenos Aires presented in this article is that the audio tour, structured to make participants move around the city, reproduces the control of mass tourism instead of creating a specific experience with the city or among the participants. The experience that the audio tour provides to these participants, in its dramaturgy, is that of the uncanny found in mass behaviour, in the human-machine relationship and in the theatricality of everyday life. It lacks, however, a critique on the socio-historical constraints affecting the production of the city space. At the end of the analysis, we also point to a contradiction on Rimini Protokoll’s mode of production in the Remote X series related to the touristic logic of international theatre festivals.